EVIDENCE BASED CASE REPORT (EBCR) PENGARUH PENGGUNAAN BIRTH BALL DALAM MENGURANGI NYERI PERSALINAN: kala I, nyeri persalinan, terapi birth ball - nur, sarah (Jurnal Kesehatan Siliwangi, 2024)
Background: In the labor process, the cervix opens and thins, and the head descends through the birth canal, uterine contractions occur with regular frequency and intensity that cause pain. Birth ball helps mothers in the first stage of labor, which aims to help the progress of labor that can be used in various positions, the use of birth ball in labor is useful in reducing pain and is a comfortable aid for laboring mothers.. Objective: Implementing the use of a birth ball can reduce the pain felt by mothers in the first stage of labor. Method: The method of writing this EBCR is by searching for evidence through data based on Pubmed and Google Scholar with publication years 2016-2023, 3 articles were obtained to be reviewed critically. Results: After an evaluation was carried out before and after the intervention using a birth ball, the mother in labor was able to reduce labor pain in the first stage. Conclusion: The use of a birth ball as a non-pharmacological intervention can be an alternative to reduce pain in mothers in the first stage of labor.